AWARENESS AND ADOPTION OF GREEN FINANCE INSTRUMENTS AMONG RETAIL CUSTOMERS IN PUNE: AN EMPIRICAL STUDY - Khalate, Santosh Balasaheb; More, Dhiresh A.; Chavan, Shekhar Sayajirao (ShodhKosh: Journal of Visual and Performing Arts, 2023)
As environmental sustainability becomes a global priority, green finance has emerged as a key instrument for promoting eco-friendly investments. This study investigates the level of awareness and adoption of green finance instruments—such as green bonds, green mutual funds, and sustainable banking products—among retail banking customers in Pune. Using a structured questionnaire and empirical analysis of responses from 100 participants, the study evaluates customer knowledge, perception, behavioral intent, and barriers to adoption. The findings suggest that while awareness of green finance is growing, actual adoption remains limited due to low financial literacy, perceived complexity, and lack of marketing by financial institutions. The study concludes with policy recommendations for banks, regulators, and NGOs to enhance awareness and encourage broader adoption among retail investors.